Management of Lateral Canthal Coloboma in Goldenhar Syndrome: A Rare Case Report: Poster Presentation - Case Report - Resident - KETUT PRAMANA ADIPUTRA; PUTU YULIAWATI; NI MADE LAKSMI UTARI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Goldenhar syndrome is a rare congenital disorder characterized by a wide range of physical anomalies affecting the face, ears, eyes, and spine. Case Illustration : Patient, female 19-year-old, complained of growing mass and blurry vision on right eye since childhood. The patient also has an asymetric face with the right side being smaller then left. She also has hearing disorder on her right ear. Ophthalmology examination revealed right eye's visual acuity is 6/120, lateral canthus coloboma , trichiasis and mass on the inferior palpebral, and conjunctiva attached to the cornea. Left eye is within normal limit. The right ear appears deformed, with no ear canal and preauricular skin tags. Patient underwent conjungtiva tumor excision and given labia mucosa graft with canthoplasty. Histology examination revealed benign lipomatous tumor. Patient feels more confident after oculoplasty surgery. Discussion : Goldenhar syndrome is a rare condition caused by abnormal development of the first and second branchial arches. It is characterized by a wide range of ocular features, including eyelid and iris coloboma, conjungtiva dermoid or dermolipoma, and more. Beside ocular features, other features are ear malformations, facial asymmetry, cleft lip or palate, and vertebral anomalies. It was unique case because an unformed canthus was found due to a large of conjunctival fornix mass. Appropriate management is necessary for a fulfilling life, though the disorder can have significant psychosocial effects. Conclusion : Goldenhar syndrome is a rare disease with numerous symptoms and its management is crucial for individuals to have a fulfilling life despite its potentially significant psychosocial impacts.